Rapid reduction in BCR‐ABL1 transcript predicts deep molecular response in dasatinib‐treated chronic‐phase chronic myeloid leukaemia patients. (16th October 2017) - Murai, Kazunori; Yamaguchi, Kohei; Ito, Shigeki; Miyagishima, Takuto; Shindo, Motohiro; Wakasa, Kentaro; Inomata, Mitsue; Nagashima, Takahiro; Kondo, Takeshi; Fujimoto, Nozomu; Yamamoto, Satoshi; Yonezumi, Masakatsu; et al.
Abstract: Objectives: We conducted a phase‐II study to evaluate the efficacy and safety of dasatinib in patients newly diagnosed with chronic‐phase chronic myeloid leukaemia (CML‐CP) in Japan (IMIDAS PART 2 study). Methods: Seventy‐nine patients were administered 100 mg dasatinib once daily. We examined pretreatment and post‐treatment influences of various factors. The BCR‐ABL1 international scale (IS), halving time (HT) and reduction rate of BCR‐ABL1 transcript within the initial 1 or 3 months of therapy (RR‐ BCR‐ABL1 1m, 3m ) were the post‐treatment factors investigated to predict the molecular response. Results: The estimated major molecular response (MMR), molecular response 4.0 (MR4.0) and molecular response 4.5 (MR4.5) rates were 77.2%, 49.4% and 35.4%, respectively, at 12 months. Grade 3/4 non‐haematologic adverse events were infrequent. Multivariate analysis showed that age >65 years was significantly correlated with MR4.0 and MR4.5 (deep molecular response: DMR) at 12 months. All post‐treatment factors at 3 months predicted DMR by univariate analysis. However, RR‐ BCR‐ABL1 3m was the only significant landmark for predicting DMR by multivariate analysis. Conclusions: Primary treatment of CML‐CP with dasatinib enabled early achievement of MMR and DMR, particularly in elderly patients, with high safety. Furthermore, RR‐ BCR‐ABL1 3m was found to be a more useful predictor of DMR than HT‐ BCR‐ABL1 and BCR‐ABL1 IS.